2016
DOI: 10.1007/s11999-015-4366-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Open Reduction and Internal Fixation versus Primary Arthrodesis Improve Patient Outcomes for Lisfranc Trauma? A Systematic Review and Meta-analysis

Abstract: Background Although Lisfranc injuries are uncommon, representing approximately 0.2% of all fractures, they are complex and can result in persistent pain, degenerative arthritis, and loss of function. Both open reduction and internal fixation (ORIF) and primary fusion have been proposed as treatment options for these injuries, but debate remains as to which approach is better. Questions/purposes We asked whether ORIF or primary fusion led to (1) fewer reoperations for hardware removal; (2) less frequent revisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 25 publications
1
65
0
1
Order By: Relevance
“…This requires surgery in nearly all cases. Failure to restore the normal anatomy promotes early post-traumatic arthritis, although this may occur even with appropriate treatment 9 10…”
Section: Discussionmentioning
confidence: 99%
“…This requires surgery in nearly all cases. Failure to restore the normal anatomy promotes early post-traumatic arthritis, although this may occur even with appropriate treatment 9 10…”
Section: Discussionmentioning
confidence: 99%
“…Intersegment rang of motion (ROM) during gait was previously found to be related to PROM in patients with foot and ankle trauma [32]. Hence, kinematic gait analysis could provide more insight into kinematic changes in patients after Lisfranc injury and in addition could lead to more information on unsolved issues such as the influence on surgical reduction on functional outcome and the best fixation method [4,[33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…However, even after appropriate treatment with ORIF, up to 40 to 94% of patients will develop post-traumatic arthritis [ 5 , 13 , 30 , 31 ], necessitating conversion to an arthrodesis to relieve pain [ 14 16 ]. To prevent the need for secondary operations and the development of post-traumatic arthritis, primary arthrodesis (PA) is suggested [ 30 , 32 34 ]. The treatment of non-dislocated injuries, in turn, is controversial [ 29 , 35 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Statistically significant differences were not found in physical functioning with regard to SF-36 or SMFA scores at any follow-up time interval. In their systematic review and meta-analysis, Smith et al [ 34 ] concluded that ORIF has a higher risk of implant removal compared with PA (risk ratio 0.23 (0.11–0.45) p < 0.001), although there were no statistically significant differences in revision surgery, PROMs or non-anatomic alignment. Cochran et al [ 32 ] organized a retrospective comparative cohort study on PA versus ORIF in young athletic military personnel with low-energy Lisfranc injury.…”
Section: Introductionmentioning
confidence: 99%